Promoting Justice, Equity, Diversity,and Inclusion (JEDI) - Efforts of the Agronomy, Crop and Soil Sciences Graduate Student Committee - Boyle, P.; Tancredi, M. T.; Eeswaran, R. (My University, 2021)
The ACS Graduate Student Committee is a group of 11+ graduate student members of the Societies. This committee primarily functions to: 1) develop programs/activities that enhance graduate student development and that assist the graduate students establish their networks, career development, and friendships; and 2) Consider broad questions of activities and programs to promote graduate student membership, value, and involvement in the Societies. This poster highlights the Graduate Student Committee's mission and objectives, and outlines actions the Committee has undertaken, or plans to undertake in the future, in order to foster an environment of justice, equity, diversity and inclusion within the Societies.